Tears of the sun - Lobell, Mike.; Rifkin, Arnold; Bryce, Ian.; Lasker, Alex.; Cirillo, Patrick; Fuqua, Antoine; Willis, Bruce, 1955-; Bellucci, Monica, 1968-; Hauser, Cole, 1975-; Skerritt, Tom.; Fiore, Mauro; Buff, Conrad; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2003)
When a doctor is rescued by a Special-Ops unit in the jungle of Nigeria, she refuses to go with them unless they agree to help rescue 70 refugees as well.
Title from container.
Special features: director's audio commentary; writer's observations; "Journey to safety: making Tears of the sun"; voices of Africa; deleted scenes; Africa fact track; interactive map of Africa; trailers.
Director of photography, Mauro Fiore ; editor, Conrad Buff ; music, Hans Zimmer ; costume designer, Marlene Stewart ; production designer, Naomi Shohan.
Bruce Willis, Monica Bellucci, Cole Hauser, Tom Skerritt.
MPAA rating: R.
DVD, Dolby digital 5.1, aspect ratio: 2.40:1.
Keywords: United States. -- Navy. -- SEALs -- Drama; Missions -- Nigeria -- Drama; War relief -- Nigeria -- Drama; Feature films; Video recordings for the hearing impaired; War films